Guía instructiva para certificación de operador económico autorizado (OEA) para las empresas importadoras (2021)
The objective of this document is to design a guide for importing companies interested in becoming certified as Authorized Economic Operators (AEO). This certification was promulgated with Decree 3568 of 2011 and currently (August 2021) only 323 companies have been certified in Colombia, which is due to the ignorance of companies whose economic activity involves the international supply chain, since they ignore the benefits that such certification offers and that would allow them to be more competitive.